1973
DOI: 10.1044/jshr.1603.367
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Rate: Effects on Children’s Comprehension of Normal Speech

Abstract: This study investigated the comprehension of speech among children in maturational stages of linguistic development when speech was presented at varying rates of utterance by a trained speaker. Five groups, each consisting of a subgroup of 10 kindergarten and a subgroup of 10 second-grade children, were presented with a tape-recorded administration of the receptive section of the Northwestern Syntax Screening Test (NSST). Each group heard the test at one or another of the following rates: 2.6, 3.4, 4.7, 5.3, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…The present findings from normal children do not support the claim of improved performance when stimuli are presented at rates faster (Woodcock & Clark 1968) or slower (Berry & Erickson 1973, Nelson 1976) than normal speech. In the present investigation the normal children repeated sentences presented at a very fast rate (60% compression or approximately 411 words per minute) as accurately as those presented at a normal rate.…”
Section: Discussioncontrasting
confidence: 76%
“…The present findings from normal children do not support the claim of improved performance when stimuli are presented at rates faster (Woodcock & Clark 1968) or slower (Berry & Erickson 1973, Nelson 1976) than normal speech. In the present investigation the normal children repeated sentences presented at a very fast rate (60% compression or approximately 411 words per minute) as accurately as those presented at a normal rate.…”
Section: Discussioncontrasting
confidence: 76%
“…Generally, a moderate rate of speech appears to facilitate intelligibility, with slightly slower rates thought to increase young children's comprehension (Berry & Erickson, 1973), although optimal vowel durations for child listeners in conversational speech or in clear speech are likely variable. Slight increases in vowel duration appear to yield the greatest intelligibility, permitting listeners to resolve a perturbed speech signal.…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence of the effects of speaking rate on listeners' speech processing abilities comes from other age groups. For instance, Nelson ͑1976͒ showed that 5-9-year-old children's comprehension of spoken sentences was significantly impaired when they listened to the sentences at a fast speaking rate ͑4.9 syllables/s͒ compared to a slower speaking rate ͑2.5 syllables/s͒ ͑see also Berry and Erickson, 1973͒. Furthermore, slower speaking rate is generally associated with better speech intelligibility in hearing-impaired populations ͑Uchanski et al, 1996͒, as well as in normal adult listeners ͑Bradlow and Pisoni, 1999͒.…”
Section: A Slow Speaking Ratementioning
confidence: 99%